Aplikasi Plasma Lucutan Berpenghalang Dielektrik pada Peningkatan Kualitas Air dengan Mengalirkan Air secara Langsung dalam Reaktor Berkonfigurasi Elektroda Spiral-Silinder - Muhlisin, Zaenul; Oktiyana, Wulandary; Nur, Muhammad (BERKALA FISIKA, 2009)
A dielectric barrier discharge plasma reactor has been realized and characterized with air source as a working gas. Ozone and dissolved ozone concentration were measured at various voltages (4 to 8 kV), treatment time ( 1 to 5 minutes), water flow rate 4.167 l/min and different air flow rates (1.5 and 2.5 l/min). And the other hand, for understand the ability of ozone to improve water quality, dissolved oxygen has been measured at various voltage (3.6 to 5.2 kV) and after treatment time (until 90 minutes). Spiral electrode is made by copper wire with circumference length 500 mm and diameters 1 mm, while cylindrical electrode is made from aluminum foil with 450 mm in length. Aluminum foil is stuck at inner wall of PVC tube with 500 mm in length and diameter 1.25 inch. Pyrex is used as dielectric material, with length 500 mm, inner diameter 10 mm and thickness 1 mm The result show ozone is produced have maximum concentration 15.613 ppm and dissolved ozone have maximum concentration 10.305 ppm. As a whole ozone concentration higher than dissolved ozone concentration. Both of ozone and dissolved ozone concentration increases by increase of the voltage applied, increases by increase treatment time and increases by decrease of the gas flow rate inside the reactor. Command dissolved oxygen increases with the increase of the high voltage applied and increases after dissociation ozone in water. Key Words : spiral cylindrical electrode, dielectric barrier discharge, the ozone concentration, the dissolved ozone concentration, dissolved oxygen